LONGITUDINAL ASSOCIATIONS BETWEEN SPOUSAL LOSS, RELIGIOUS INVOLVEMENT, AND COGNITIVE HEALTH IN LATER LIFE. (20th December 2022) - Yu, Xinfang; Lee, Hyo Jung
Abstract: Death of a spouse is one of the major stressors which is more frequently observed in one's late life. Previous literature showed a link between the death of a spouse and late-life cognitive health and suggested a benefit of having more religious involvements. Applying Stress Process Model, this study examines multiple dimensions of religious involvements and whether they buffer a negative impact of spousal loss on cognitive health in old age. Using data from the Health and Retirement Study (2006 – 2016 waves), we selected older adults who were married at baseline (N = 6658). We conducted a) regression analyses to examine the main effect of spousal loss on cognitive health as well as buffering effect of religious involvement and b) growth curve modeling to analyze the trajectories of cognitive functions. Preliminary analyses showed that spousal loss in late life was associated with poorer cognitive function among older adults at baseline and follow-ups. More frequent attendance at religious services and prayer in private setting were associated with better cognitive function, yet, no buffering effect was found. We observed a gradual decline in cognitive function over time among the widowed respondents. Findings confirm that widowed individuals are more likely to experience cognitive decline over time, compared to married counterparts. While religious involvement might not mitigate the negative impact of spousal loss on cognition, the study supports that each dimension of religious involvement may exert different outcomes in terms of older individual's cognitive health during widowhood.